Asosiasi Pengeluaran Pemerintah Dengan Pembangunan Bidang Kesehatan Di Provinsi Jawa Timur - Muhammad Guzali Tafalas (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
This study aims to analyze the positive association of government expenditure on health (PK) with Maternal Mortality Rate (AKIM) and Infant Mortality Rate (IMR) with government expenditure on education in East Java Province. Analysis of the data in this study uses the analysis of ARIMA multivariate time series models. The ARIMA model has three modeling parameters, namely: (1) Autoregressive or AR processes, (2) Integrated or I processes, and (3) Moving Average or MA processes. The results showed that the reduction in infant mortality rate (IMR) was positively associated with the East Java Provincial government spending on health (PBK) and government spending on health was not significantly associated with the reduction in maternal mortality (AKIM).